2018
DOI: 10.1155/2018/1916841
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 Signaling‐Triggered PI3K Mediates Mitochondrial Protection to Participate in Early Cardioprotection by Exercise Preconditioning

Abstract: Previous studies have shown that early exercise preconditioning (EEP) imparts a protective effect on acute cardiovascular stress. However, how mitophagy participates in exercise preconditioning- (EP-) induced cardioprotection remains unclear. EEP may involve mitochondrial protection, which presumably crosstalks with predominant H2O2 oxidative stress. Our EEP protocol involves four periods of 10 min running with 10 min recovery intervals. We added a period of exhaustive running and a pretreatment using phosphoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…The protein levels of Beclin 1 were downregulated for the ET group at 0 h but without significant alteration at 6 h. Furthermore, the ET group showed lower values of ATG5 at 6 h. Yuan et al [ 54 ] did not observe modifications in Beclin 1 in the heart tissue of rats after acute exhaustive treadmill running. Campos et al [ 55 ] blocked the autophagic flux with chloroquine and visualized an increase in LC3II, Sqstm1/p62, and Beclin 1 in control animals, but not in heart failure animals.…”
Section: Discussionmentioning
confidence: 97%
“…The protein levels of Beclin 1 were downregulated for the ET group at 0 h but without significant alteration at 6 h. Furthermore, the ET group showed lower values of ATG5 at 6 h. Yuan et al [ 54 ] did not observe modifications in Beclin 1 in the heart tissue of rats after acute exhaustive treadmill running. Campos et al [ 55 ] blocked the autophagic flux with chloroquine and visualized an increase in LC3II, Sqstm1/p62, and Beclin 1 in control animals, but not in heart failure animals.…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that late exercise preconditioning protected the heart from exhaustive exercise-caused injuries through increasing Parkin-mediated mitophagy [114]. It was further suggested that exercise preconditioning augmented mitophagy via H 2 O 2 oxidative stress-induced activation of PI3K [115]. Consistent with this view, it was found that earlier aerobic exercise complemented by a natural herb Rhodiola sacra protected the cardiac and skeletal muscles in exhaustive exercise through enhanced mitophagy [116].…”
Section: Mitophagy and Exercisementioning
confidence: 90%
“…43) Our past reports indicated that the blocked autophagy is associated with aggravated structural injury in cell and organelle. 33,34) Therefore, these results may explain how EE impairs autophagosome clearance and leads to the accumulation of LC3-II and p62, which, in turn, increases the proteotoxicity of misfolded/ damaged proteins and aggravates the myocardial ischemichypoxic injury.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms have been previously demonstrated for their participation in EP-induced cardioprotection. 33,34) Bcl-2 is another key regulator of exercise-induced autophagy. 18) Under normal conditions, Beclin1 is inhibited by Bcl-2, whereas under stress, it dissociates from Beclin1-Bcl-2, thus, enabling the activation of PI3KC3, which induces autophagy.…”
Section: Discussionmentioning
confidence: 99%